1999
DOI: 10.1007/s004390050993
|View full text |Cite
|
Sign up to set email alerts
|

Association of the human NPPS gene with ossification of the posterior longitudinal ligament of the spine (OPLL)

Abstract: OPLL (ossification of the posterior longitudinal ligament of the spine) is a common form of human myelopathy with a prevalence of as much as 4% in a variety of ethnic groups. To clarify the genetic factors that predispose to OPLL, we have studied ttw (tiptoe walking), a mouse model that presents ectopic ossification of the spinal ligaments similar to OPLL and have found that the ttw phenotype is caused by the nonsense mutation of the gene encoding nucleotide pyrophosphatase (NPPS), a membrane-bound glycoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 19 publications
1
114
1
1
Order By: Relevance
“…Interestingly, these genes included Dmp1, Ank, and Enpp1, all of which are known to play key roles in the process of extracellular matrix mineralization not only in mice but also in humans. (35)(36)(37)(38)(39)(40)(41)(42)(43) Moreover, since we observed that, at least relative to Alpl, all three genes were expressed at lower levels in Mdk-deficient osteoblasts, it is reasonable to speculate that these results provide a molecular explanation for the skeletal phenotype of Mdk-deficient mice. As discussed below, this is particularly true for Ank and Enpp1, whereas the decreased expression of Dmp1 rather should result in other abnormalities.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, these genes included Dmp1, Ank, and Enpp1, all of which are known to play key roles in the process of extracellular matrix mineralization not only in mice but also in humans. (35)(36)(37)(38)(39)(40)(41)(42)(43) Moreover, since we observed that, at least relative to Alpl, all three genes were expressed at lower levels in Mdk-deficient osteoblasts, it is reasonable to speculate that these results provide a molecular explanation for the skeletal phenotype of Mdk-deficient mice. As discussed below, this is particularly true for Ank and Enpp1, whereas the decreased expression of Dmp1 rather should result in other abnormalities.…”
Section: Discussionmentioning
confidence: 72%
“…playing a role in the regulation of extracellular matrix mineralization in mice and humans. (36)(37)(38)(39)(40)(41)(42)(43) In contrast, Mdk did not affect the expression of other osteoblast marker genes, such as Ibsp (encoding bone sialoprotein), Alpl (encoding tissuenonspecific alkaline phosphatase), and Bglap (encoding osteocalcin). To confirm these data, we next performed quantitative RT-PCR using independently isolated cultures and found a significant induction of Dmp1, Ank, and Enpp1 expression following Mdk administration, whereas expression of Alpl was reduced significantly (Fig.…”
Section: Increased Cortical Bone Resorption In Aged Mdk-deficient Micementioning
confidence: 93%
“…OPLL is a common disorder in Asia, particularly in Japan, where the incidence is 1.5% among people over 50 years of age. Polymorphisms of the PC-1 gene, of currently unknown functional significance, have been reported in Japanese subjects with OPLL (40,41). The PC-1 KO mice are also an accepted animal model for diffuse idiopathic skeletal hyperostosis and ankylosing spinal hyperostosis (refs.…”
Section: Discussionmentioning
confidence: 99%
“…25 The entire coding region cDNA sequence of B10/PDNP3, and partial cDNA sequence of autotaxin (limited to domains encompassing the catalytic site and EF hand domain) also were determined using primers that spanned the cDNA regions, generating amplicons of 200 to 350 bp. All polymerase chain reaction products were electrophoretically separated, extracted, and then purified using Qiagen (Valencia, CA) gel extraction columns.…”
Section: Sequencing Of Pc-1 B10/pdnp3 and Autotaxinmentioning
confidence: 99%